How Language and Technology Can Improve Student Learning Quality in Engineering? Definition, Factors for Enhancing Students Comprehension, and Computational Bibliometric Analysis - Dwi Fitria Al Husaeni; Dwi Novia Al Husaeni; Risti Ragadhita; Muhammad Roil Bilad; Abdulkareem Sh. Mahdi Al-Obaidi; Asep Bayu Dani Nandiyanto (Universitas Negeri Makassar, 2022)
The research aims to review developments in language and technology research that can improve the quality of teaching and learning in engineering. Several factors that can influence the teaching and learning process are explained, supported by a bibliometric analysis (with keywords “Language” AND “Engineering Learning” from Google Scholar from 2020 to 2022). The review includes the definition of engineering education with technology's advantages in engineering education. We also explained about purpose and service of language with what considerations in making strategies in language and technology for teaching and learning engineering education. Explanations about formal and informal learning as well as education level to learn engineering and curriculum development were also added. The application of technology in media and laboratories is also the main factor in improving literacy and language's impact on students. All factors cannot be separated from language and student characteristics, motivation, teacher-student relationships, therapy, and psychological condition. We also added information regarding language barriers for students with special needs and new language-improving technology for teaching. The results of the co-occurrence analysis expressed several points to be considered, including children, mathematics, STEM, education, and educators’ terms. Thus, it obtained that the principle of engineering education refers to the process of teaching and learning about scientific concepts, principles, and practices, and technology plays an important role because it is closely related to scientific principles and investigative methods. Language has an important role in supporting students' understanding and abilities in this subject since it conveys learning information. This paper can be used as a reference for educators to understand current conditions regarding the importance of language in the teaching and learning in the engineering field.